SEXUAL VIOLENCE AGAINST WOMEN: THE IMPORTANCE OF NURSING IN VICTIM CARE - Oliveira de Souza, Gabrielly; Rodrigues Vieira, Edineia; Carolina Salustino, Maria; Allyson Gomes Ferreira, Jefferson (Health and Society, 2023)
Objective: To demonstrate the number of cases of sexual violence against women and the importance of nursing care. Method: This is a bibliographic research, where articles in Portuguese were searched from the year 2016 to 2021, original articles available in full, in online format were included. Results: The study revealed that since the year 1980 that in Brazil there have been discussions about sexual violence, technical standard was created having as objective the care of these victims. Conclusion: It is important to emphasize that nurses are extremely important in assisting and welcoming women victims of sexual violence, since they are in the front line of care and can positively impact the identification process, as well as welcoming the woman to feel comfortable in such a situation.